ANALISIS KERENTANAN SOSIAL EKONOMI MASYARAKAT KECAMATAAN SEMARANG TENGAH TERHADAP PANDEMI COVID 19 - Sundaro, Hendrianto; Pamungkas, Wardana Galih (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2024)
Recently, the Government of Indonesia has revoked the status of the Covid 19 Pandemic. Even so, the pandemic event has sparked critical questions, “how can the city government prepare itself if in the future it is faced with a similar event?